2019
DOI: 10.1111/jcmm.14616
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and pathways associated with different immune statuses of hepatitis B virus infection

Abstract: We aimed to identify key genes and pathways associated with different immune statuses of hepatitis B virus (HBV) infection. The gene expression and DNA methylation profiles were analysed in different immune statuses of HBV infection. Differentially expressed genes (DEGs) and differentially methylated genes (DMGs) were identified, followed by their functional and integrative analyses. The differential expression of IgG Fc receptors (FcγRs) in chronic HBV‐infected patients and immune cells during different stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…FcγRIIb is an inhibitory receptor, works as a regulation molecule of the immunosystem, and is vital for the progression of various autoimmune diseases and infectious diseases. In our previous study, we performed qRT-PCR assay to identify FcγRIIb mRNA expression in HBV sufferers [22]. The study showed that FcγRIIb expression was higher in the HBV carrier group in contrast to the CHB group.…”
Section: Discussionmentioning
confidence: 99%
“…FcγRIIb is an inhibitory receptor, works as a regulation molecule of the immunosystem, and is vital for the progression of various autoimmune diseases and infectious diseases. In our previous study, we performed qRT-PCR assay to identify FcγRIIb mRNA expression in HBV sufferers [22]. The study showed that FcγRIIb expression was higher in the HBV carrier group in contrast to the CHB group.…”
Section: Discussionmentioning
confidence: 99%
“…FcγRIIb is an inhibitory receptor that functions as a regulation molecule in the immune system and is vital in the progression of various autoimmune diseases and infectious diseases. In our previous study, we performed qRT-PCR assay to assess FcγRIIb mRNA expression in HBV infected patients [ 25 ]. The study showed that FcγRIIb expression was higher in the HBV carrier group than in the CHB group.…”
Section: Discussionmentioning
confidence: 99%
“…IgG3 was also higher compared with that of HCs, but without significance. IgG serves a pivotal role in viral neutralization ( 49 ). Antigens can trigger B-cells directly, leading to a plethora of secondary signals that regulates cell differentiation and subsequent antibody production ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antigens can trigger B-cells directly, leading to a plethora of secondary signals that regulates cell differentiation and subsequent antibody production ( 50 , 51 ). The induction of specific IgG1 and IgG3 antibodies is therefore more likely to achieve the clearance of HBV and HCV ( 49 ).…”
Section: Discussionmentioning
confidence: 99%